THE EFFECTIVENESS OF INTERNAL AUDITING IN THE PUBLIC SECTOR IN ZAMBIA - Mwanza , Olivia; Kaira, Benjamin (Journal of Accounting, 2022)
Purpose: This paper aims at examining factors that have an impact on internal audit effectiveness in the public sector. The objective of this study was to device a model that can be used in the public sector to enhance a sound internal auditing system that will boost financial accountability and quality audit work. The study focused on three independent variables such as management support for internal audit activity, organizational independence on the internal audit work, and the adequate of competent internal audit staff. Methodology: In order to achieve this, a quantitative survey research design was chosen as the research paradigm underpinning the study using structured questionnaires as data collection tool to a sample of 172 respondents comprising of internal auditors and users of internal audit services who were systematically randomly sampled. Results: The study findings revealed that both management support and organizational independence were low and that internal audit office of the sampled ministries and parastatals had low technical staff proficiency which limited its capacity to provide effective service. In line with the findings, the study recommended that: (i) the management should appreciate the role of IA by providing the necessary resources and trainings. (ii) Government should ensure that the independence of IA is guaranteed for them to work without fear or interference. (iii) Government should recruit and retain Internal Audit candidates based on their qualifications, experience, training attained and certification by the IIA. The research is limited with the issue of generalizability on other settings; therefore, a similar study can be conducted in the private sector using a mixed method approach.